A new fluorometric method for the determination of pyridoxal 5′-phosphate - Srivastava, Satish K.; Beutler, Ernest (Biochimica et biophysica acta, 1973)
A new fluorometric method using semicarbazide for the determination of pyridoxal and pyridoxal 5′-phosphate (PLP) in whole blood, red cells and plasma has been developed. Semicarbazide breaks the Schiff base of PLP and proteins by “trans-Schiffization” reaction and forms semicarbazone of PLP. The semicarbazone of PLP emits strongly at 460 nm when excited at 380 nm. Several metabolic intermediates were tested for the possible interference. Only pyridoxal was found to interfere. The interference can be corrected since pyridoxal emits at 380 nm when excited at 320 nm. Using this method we found that rabbit red cells in vivo are freely permeable to PLP.